Creating a Culture for Publication Through Education and Mentoring. Issue 2 (April 2015) - Rees, Susan; Payne, Judith; Houlahan, Beth
Abstract : Nursing administrators and researchers are well positioned to achieve innovative progress in clinical practice, leadership, and research through creating a culture of publication. Direct care nurses and advanced practice nurses often have fresh ideas about delivery of patient care but may consider publication of those ideas and results an impossible task. Creating a culture for publication can be challenging. By using a change model and focusing on mentoring, role modeling, education, securing appropriate resources, and celebration/recognition as key components, this important culture can be created.